The status of birth preparedness and complication readiness among rural Indian mothers. - , Rajib Saha; Aditya Prasad Sarkar,; Indranil Saha,; Raghunath Misra,; Samir Dasgupta,; Supantha Chatterjee, (Universiti Kebangsaan Malaysia, 2014)
A cross-sectional study was conducted with the aim to explore the present status of birth preparedness and complication readiness in rural area of West Bengal and determine the possible factor(s) influencing their knowledge and practice regarding this concern.Thirty villages with homogenous characteristics were identified by cluster sampling methods from a rural block (Bhatar, Burdwan district, West Bengal) of India on April 2013 to November 2013. From every cluster 7 mothers who had delivered baby within the last year and were available first,interviewed consecutively using a guided questionnaire adapted from JHPIEGO Maternal and Neonatal Health Programme survey tools. Multivariate logistic regression was applied in analysis to predict how much the independent variables influenced the birth preparedness of mothers.62.4% mothers were found to be well prepared. Trained birth attendants and health facilities were identified before delivery in 81.9% and 78.1% cases respectively. Mode of transportation for complication management or delivery was pre-decided by about 60% of family. Only 35.7% family saved money for the same purpose. Logistic regression revealed that well preparedness increased 11 times with every new pregnancy, but it did not depend on caste and education status of the mothers.The overall birth preparedness status of the rural mothers is poor and they acquire more knowledge regarding birth preparedness from their self experience rather than from existing health system.